Cerebral and Functional Aging: First Results on Prevalence and Incidence of the Paquid Cohort - Letenneur, L.; Jacqmin, H.; Commenges, D.; Barberger-Gateau, P.; Dartigues, J.-F.; Salamon, R. (Methods of Information in Medicine, 1993)
Paquid is an interdisciplinary study designed to investigate cerebral and functional aging. A cohort of 3,777 community residents living in two administrative areas of South-Western France was selected. A standardized questionnaire was administered at home by trained psychologists. The same procedure was applied one and three years after the baseline data collection. The identification of demented subjects was made with a two-step procedure. The first step is a systematic screening by the psychologists using the DSM-III criteria for dementia. Subjects who fulfilled the DSM-III criteria were examined by a neurologist. Diagnosis of dementia is confirmed according to the NINCDS-ADRDA criteria. The Paquid cohort is complemented by a random sample of 357 institutionalized subjects. First results of prevalence and incidence rates show an exponential increase of dementia with age.
Keywords: Epidemiology; Aging; Dementia; Prevalence; Incidence